Profile of Critical Thinking Ability of Junior High School Students on Human Blood Circulation System Materials in Situbondo District - Nurul Azizah; Sutarto Sutarto; Jekti Prihatin (Eduvest - Journal of Universal Studies, 2021)
This study aims to describe the critical thinking skills of junior high school students on the subject of the Human Circulatory System in Situbondo Regency. This type of research is descriptive quantitative by using critical thinking test questions. The number of respondents in this study amounted to 236 students in 5 schools in Situbondo Regency. The critical thinking test questions on the material of the human circulatory system are in the form of multiple choices and consist of five questions according to the critical thinking indicators according to Ennis. The results of the critical thinking test of junior high school students in Situbondo Regency with the material of the human circulatory system showed an average score of 47%, for the indicator of the ability to provide simple explanations an average of 54%, the indicator of ability to build basic skills an average of 48%, the indicator of ability to conclude an average of 48%, the indicator of ability to provide further explanation an average of 49%, and the indicator of ability to set strategy and tactics an average of 37%.